مظاهر الاهتمام بتطبيق المواصفات العالمية للجودة - سليماني مليكة (جامعة الوادي University Of Eloued, 2024)
شهادة الجودة تعتبر كدليل لمطابقة المنتج للمواصفات العالمية من حيث مستوى الجودة والسلامة والامن، لذلك فتطبيق نظام الجودة يكسب المؤسسة مجموعة من الخصائص الإستراتيجية لمستقبل المنظمة و موقفها التنافسي من خلال الاستثمار في عمليات التحسين المستمر للمنتجات و العمليات الداخلية و الإبداع و الابتكار في مجال الإنتاج و العمليات ، بالإضافة إلى الاستغلال الأمثل للطاقات و القدرات البشرية و المالية التي تمتلكها مما يؤدي إلى التميز في السوق. من خلال هذه الدراسة تبين لنا ان الجزائر من بين الدول التي تسعى للوصول الى الاسواق العالمية مما دفعها الى وضع عدة قرارات لدعم وتشجيع نظام الجودة، ولكن رغم هذا بينت الاحصائيات وجود تذبذب في عدد شهادات الجودة الممنوحة خاصة في مجال الجودة البيئية . Quality certificate is considered as proof to ensure that the product conforms to international standards in terms of the level of quality, safety and security. Therefore, implementing a quality system earn the organization is a set of strategic characteristics for the future of the organization and its competitive, by investing in Continuous product improvement processes and internal processes, creativity and innovation in the field of production and operations. In addition to optimal exploitation of the human and financial energies and capabilities it possesses which leads to excellence in the market. Through this study, we found that Algeria is among the countries seeking to access global markets which prompted it to put in place several decisions to support and encourage the quality system. However, despite this, statistics show that there is Fluctuation In the number of quality certificates granted, especially in the field of environmental quality.
Demonstrations of interest in applying international quality standards
Keywords: الجودة; المنافسة; التحسين المستمر; التكاليف; quality; competContinuous improvementition; Continuous improvement; costs